Melanin-concentrating hormone receptor 1 polymorphisms are associated with components of energy balance in the Complex Diseases in the Newfoundland Population: Environment and Genetics (CODING) study. Issue 2 (4th December 2013) - Fontaine-Bisson, Bénédicte; Thorburn, James; Gregory, Anne; Zhang, Hongwei; Sun, Guang
ABSTRACT: Background: The melanin-concentrating hormone receptor 1 (MCHR1) is a G protein–coupled receptor that regulates energy balance and body composition in animal models. Inconsistent effects of MCHR1 polymorphisms on energy homeostasis in humans may partly be attributable to environmental factors. Objectives: We examined the effect of 4 single nucleotide polymorphisms (rs133073, rs133074, rs9611386, and rs882111) in the MCHR1 gene on body composition as well as energy-related lifestyle factors (diet and physical activity). We also examined the effect of gene-lifestyle interactions on body composition. Design: A total of 1153 participants (248 men and 905 women) from the cross-sectional Complex Diseases in the Newfoundland Population: Environment and Genetics (CODING) study were genotyped by using probe-based chemistry validated assays. Diet and physical activity were estimated by using validated frequency questionnaires, and body composition was assessed by using dual-energy X-ray absorptiometry. Results: Three polymorphisms (rs9611386, rs882111, and rs133073) were associated with differences in body-composition measurements (all P < 0.05). There was an interaction between rs9611386 and carbohydrate intake on total mass and waist circumference (both P ≤ 0.01). There was also an interaction between rs9611386 and body mass index categories (normal weight, overweight, and obese) on energy intakes ( P = 0.02). A similar interaction was shown with rs882111 ( P = 0.02). Interactions were also observed between each of these polymorphisms (rs9611386, rs882111, and rs133073) and physical activity score on body-composition measurements (all P < 0.05). Conclusion: These findings suggest that polymorphisms in the MCHR1 gene are associated with differences in body composition and interact with physiologic and energy-related lifestyle factors.